Response Behavior in Work Stress Surveys: A Qualitative Study on Motivational and Cognitive Processes in Self- and Other-Reports. Issue 1 (2nd January 2021) - Greulich, Berit; Debus, Maike E.; Kleinmann, Martin; König, Cornelius J.
ABSTRACT: Work stressors have major consequences for employees' health and performance. Although organizations often ask employees to fill out work stress surveys regarding stressors and resources, the literature on survey responding offers only limited advice on how to formulate work stress surveys. Furthermore, self-, supervisor-, and co-worker-reports show only low convergence. To deepen our understanding of motivational and cognitive processes when individuals respond to work stress surveys, we used a qualitative, grounded theory approach. We interviewed employees after they responded to representative items, asking them about their thoughts, motivational processes, potential factors that might have biased their responses, and the contexts they considered when responding. Since organizations are often also interested in other-reports of stress at work, we also interviewed supervisors and co-workers. We reached theoretical saturation after 31 interviews. A multi-stage coding-process with three raters resulted in new theoretical findings regarding motivational processes, comparisons, and differences between self- and other-reports. For example, employees sometimes deliberately distort answers for fear of consequences. Furthermore, employees, supervisors, and co-workers undergo different comparison processes. The findings of this study suggest that more specific and context-rich wording of items may lead to a more reliable and comparable assessment of stressors and resources at work.